PENGARUH CURRENT RATIO (CR), RETURN ON ASSETS (ROA) DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN HARGA SAHAM SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI PERIODE 2022-2024 - M. Hartono Cahyo Wijoyo; Ika Wahyuni; Ida Subaida (Fakultas Ekonomi dan Bisnis, 2026)
This study aims to determine the effect of Current Ratio (CR), Return on Assets (ROA), and Capital Structure on firm value, with stock price as an intervening variable, in property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the period 2022-2024. This study employed purposive sampling and selected 11 sample companies. The data analysis tool used in this study was smartPLS 3.0. The data analysis methods employed in this study included classical assumption tests consisting of multicollinearity and normality tests, coefficient of determination tests, structural equation analysis (inner model), and research hypothesis testing. The results of the direct effect hypothesis test indicate that Current Ratio (CR) has a negative but insignificant effect on stock price, Return on Assets (ROA) has a positive but insignificant effect on stock price, and Capital Structure has a negative but insignificant effect on stock price. Furthermore, Current Ratio (CR) has a positive but insignificant effect on firm value, Return on Assets (ROA) has a significant positive effect on firm value, and Capital Structure has a negative but insignificant effect on firm value. Meanwhile, stock price has a significant positive effect on firm value. The results of the indirect effect test indicate that the Current Ratio (CR) on firm value through stock price has a negative but insignificant effect, Return on Assets (ROA) on firm value through stock price has a positive but insignificant effect, and capital structure on firm value through stock price has a negative but insignificant effect.